Entrepreneurial behaviour of youth and its influencing factors: A systematic review - Arunkumar, R; Murugan, P P; Senthilkumar, M; Chandrakumar, M; Senguttuvan, K; Gangai , S R; Dhivya, C (Plant Science Today, 2025)
The entrepreneurial behaviour of youth is a critical area of research due to its potential to drive economic growth, innovation and societal progress, particularly in addressing youth unemployment. This study conducts a systematic literature review and bibliometric analysis to examine the determinants of entrepreneurial behaviour among youth. Utilizing reputable academic databases such as Scopus, Web of Science and Google Scholar, 72 relevant studies were identified and analyzed using tools like VOSviewer and R Studio to map research trends and thematic clusters. The Preferred Reporting Items for Systematic Reviews and Meta-Analyses (PRISMA) systematically documented the selection process. The analysis highlights a significant increase in research output between 2021 and 2024, with journals like Sustainability (Switzerland) and SAGE Open emerging as leading contributors. The thematic analysis underscores the importance of entrepreneurial self-efficacy, education, policy frameworks and resource access in shaping youth entrepreneurship. Additionally, interdisciplinary influences from psychology and technology fostered entrepreneurial tendencies. The study also explores geographical variations, revealing that sociocultural and economic ecosystems significantly impact entrepreneurial behaviour. The findings reveal that entrepreneurial behaviour is influenced by a range of factors, including personal traits and external factors such as family entrepreneurial tradition, access to credit, education and relational support. This study provides valuable insights for researchers, policymakers and practitioners to design targeted strategies that empower youth and promote sustainable entrepreneurial ecosystems globally.